Analisis Pengaruh Firm Size, DER, Asset Growth, ROE, EPS, Quick Ratio dan Past Dividend terhadap Dividend Payout Ratio (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2011-2015) - Simbolon, Kristina; Sampurno, R. Djoko (Faculty of Economics and Business Diponegoro University, 2017)
This study is perfomed to examine the effect of Firm Size, Debt to Equity Ratio (DER), Asset Growth, Return on Equity (ROE), Earning per Share (EPS), Quick Ratio and Past Dividend (DPR_1) toward Dividend Payout Ratio (DPR) manufacture companies that is listed in BEI over period 2011-2015. Sampling technique used here is purposive sampling. The data obtained based on financial statement publication on IDX and ICMD from Indonesian stock exchange, www.idx.co.id. It is gained sample amount 26 companies from 145 manufacture companies those are listed in BEI. The analysis technique used here is multiple regression and level significance 5%. The result form analisys, it indicates that DER and Asset Growth variable partially has negatif significant toward DPR, ROE and DPR_1 partially has positive significance. Firm Size, EPS and Quick Ratio variable partially not significant toward DPR of the company in BEI on 2011-2015. While simultaneously Firm Size, DER, Asset Growth, ROE, EPS, Quick Ratio and DPR_1 proof significantly influent DPR.